PENGARUH TEKNOLOGI PERTANIAN TERHADAP PRODUKTIVITAS HASIL PANEN PADI DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Akhwan Ali (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to find out how the influence of agricultural technology on the productivity of rice harvest in Kecamatan Maritengngae Sidenreng Rappang Regency, and to determine the factors that influence it. Research location in Kecamatan Maritengngae Sidenreng Rappang Regency. This research was conducted for 2 (two) months ie October to November 2016, the research design used is a quantitative approach. Population in this study is all farmers in District Maritengngae Sidenreng Rappang Regency as many as 7015 people. The sample in this study is using yount table that takes 3% of the population there are as many as 210 people. Data collection techniques used are observations, questionnaires, interviews, and library research (documentation). Data obtained then processed using descriptive statistical analysis techniques with the help likert scale. that the influence of agricultural technology on the productivity of rice crops in Kecamatan Maritengngae Sidenreng Rappang Regency amounted to 70% with the category of